2015
DOI: 10.1155/2015/245328
|View full text |Cite
|
Sign up to set email alerts
|

TopicalHypericum perforatumImproves Tissue Regeneration in Full-Thickness Excisional Wounds in Diabetic Rat Model

Abstract: Delayed wound healing process is one of the most important concerns in diabetes. Healing of wounds has four phases, namely, hemostasis, inflammation, proliferation, and remodeling. For a successful repair, all four factors must occur properly. Hence, we aimed to evaluate the healing effects of Hypericum perforatum (HP) on full-thickness diabetic skin wounds by using stereological methods. Forty-eight female diabetic rats were randomly divided into four groups (n = 12): gel base treated group, HP 5% gel treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…1 [62, 6570]; 2 [53, 7678, 138152]; 3 [66, 68, 93, 97, 98, 100, 153157]; 4 [158]; 5 [38, 93, 118, 119, 123–126, 157, 159–169]; 6 [170]; 7 [171]; 8 [172]; 9 [102, 103, 173]; 10 [174];; 11 [93]; 12 [93, 117–119]; 13 [167] 14 [65, 69, 175]; 15 [76, 79, 139–141, 151, 177, 178, 176, 179]; 16 [97]; 17 [120122]; 18 [68]; 19 [78, 138, 152, 170]; 20 [68, 102, 103]; 21 [160, 166, 180]; 22 [79, 149, 150]; 23 [168, 181]; 24 [82]; 25 [35, 37, 104]; 26 [182]; 27 [29, 5763]; 28 [31, 32, 82, 84, 87, 88, 183, 184]; 29 [104]; 30 [81]; 31 [185]; 32 [29, 64, 186]; 33 […”
Section: Resultsmentioning
confidence: 99%
“…1 [62, 6570]; 2 [53, 7678, 138152]; 3 [66, 68, 93, 97, 98, 100, 153157]; 4 [158]; 5 [38, 93, 118, 119, 123–126, 157, 159–169]; 6 [170]; 7 [171]; 8 [172]; 9 [102, 103, 173]; 10 [174];; 11 [93]; 12 [93, 117–119]; 13 [167] 14 [65, 69, 175]; 15 [76, 79, 139–141, 151, 177, 178, 176, 179]; 16 [97]; 17 [120122]; 18 [68]; 19 [78, 138, 152, 170]; 20 [68, 102, 103]; 21 [160, 166, 180]; 22 [79, 149, 150]; 23 [168, 181]; 24 [82]; 25 [35, 37, 104]; 26 [182]; 27 [29, 5763]; 28 [31, 32, 82, 84, 87, 88, 183, 184]; 29 [104]; 30 [81]; 31 [185]; 32 [29, 64, 186]; 33 […”
Section: Resultsmentioning
confidence: 99%
“…Parts were embedded in a cylindrical paraffin block. Isotropic uniformly random (IUR) sections of the blocks with 5 μm and 15 μm width were obtained 16 and blemished with both Hedenhain’s azan and hematoxylin-eosin stains.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical efficacies of H. perforatum extracts in the therapy of mild to moderate depression have been confirmed in many studies (Lecrubier et al, 2002 ; Butterweck, 2003 ). Many other important pharmaceutical properties of H. perforatum including antiviral (Schinazi et al, 1990 ), anticancer (Agostinis et al, 2002 ), neuroprotective (Silva et al, 2004 ), antioxidant (Silva et al, 2005 ), and wound healing (Yadollah-Damavandi et al, 2015 ) activities have also been reported. Since treating humans and animals with H. perforatum extracts does not result in any serious adverse side effects (Trautmann-Sponsel and Dienel, 2004 ), use of this medicinal herb has increased dramatically during the past decade.…”
Section: Introductionmentioning
confidence: 99%